Comparison of Lamiaceae medicinal uses in eastern Morocco and eastern Andalusia and in Ibn al-Baytar's Compendium of Simple Medicaments (13th century CE). (18th April 2017) - El-Gharbaoui, Asmae; Benítez, Guillermo; González-Tejero, M. Reyes; Molero-Mesa, Joaquín; Merzouki, Abderrahmane
Abstract: Ethnopharmacological relevance: Transmission of traditional knowledge over time and across culturally and historically related territories is an important topic in ethnopharmacology. Here, we contribute to this knowledge by analysing data on medicinal uses in two neighbouring areas of the Western Mediterranean in relation to a historical text that has been scarcely mentioned in historical studies despite its interest. Aim of the study: This paper discusses the sharing of popular knowledge on the medicinal uses of plants between eastern Morocco and eastern Andalusia (Spain), focusing on one of the most useful plant families in the Mediterranean area: Lamiaceae. Moreover, we used the classical work of Ibn al-Baytar (13th century CE) The Compendium of Simple Medicaments and Foods as a basis to contrast the possible link of this information, analysing the influence of this historical text on current popular tradition of medicinal plant use in both territories. Materials and methods: For data collection, we performed ethnobotanical field research in the eastern part of Morocco, recording current medicinal uses for the Lamiaceae. In addition, we systematically reviewed the ethnobotanical literature from eastern Andalusia, developing a database. We investigated the possible historical link of the shared uses and included in this database the information from Ibn al-Baytar's Compendium . To compare the similarity and diversity of the data, we used Jaccard's similarity index. Results: Our field work provided ethnobotanical information for 14 Lamiaceae species with 95 medicinal uses, serving to treat 13 different pathological groups. Of the total uses recorded in Morocco, 30.5% were shared by eastern Andalusia and found in Ibn al-Baytar's work. There was a higher similarity when comparing current uses of the geographically close territories of eastern Morocco and eastern Andalucía (64%) than for eastern Morocco and this historical text (43%). On the other hand, coincidences between current uses in eastern Andalusia and the ones related in the Compendium are lower, 28%. Conclusions: The coincidence of the current ethnobotanical knowledge in the two territories is high for the Lamiaceae. Probably the shared historical background, recent exchanges, information flow, and the influence of the historical herbal texts have influenced this coincidence. In this sense, there is a high plant-use overlap between Ibn al-Baytar's text and both territories: nearly half of the uses currently shared by eastern Morocco and eastern Andalusia were included in the Compendium and are related to this period of Islamic medicine, indicating a high level of preservation in the knowledge of plant usage. The study of 14 species of Lamiaceae suggests that this classical codex, which includes a high number of medicinal plants and uses, constitutes a valuable bibliographical source for comparing ancient and modern applications of plants. Graphical abstract: